Três ensaios em análise econômica - Benegas, Maurício (2006)
This Thesis studies three distinct problems between itself, even so connected for the instrument. In the first chapter a model of endogenous technical progress is used to study the relations between growth of the agricultural productivity and the process of industrialization in a context of open economy. The concept of Dynamic Comparative Advantage is exhaustingly used and, additionally, searchs to understand as the technological integration between the sectors agricultural and industrial contributed for the dynamics of the employ in the industry. In the second chapter a model of general equilibrium was used to analyze and to compare the effect of two fiscal adjustment rules: the rule of primary superávit proportional to the product and the rule of zero nominal deficit . In the constructed model the rules it was analyzed the impacts of these rules on the optimal allocations as well as on the welfare. In both the cases, the effect of short and long runs always are compared. Finally, the third chapter considers an alternative proofs of the Hotelling´s Lemma and Shephard´s Lemma using new relations of duality in the theory of the production. The proofs proposals possess two advantages, relatively to the usual demonstrations, which are, not the use of the known Enveolpe Theorem and the validity of the demonstration for interior points to the production set.